Fluorine Substituted Bithiophene Imide‐Based n‐Type Polymer Semiconductor for High‐Performance Organic Thin‐Film Transistors and All‐Polymer Solar Cells. Issue 2 (23rd November 2018) - Sun, Huiliang; Tang, Yumin; Guo, Han; Uddin, Mohammad Afsar; Ling, Shaohua; Wang, Ruizhi; Wang, Yingfeng; Zhou, Xin; Woo, Han Young; Guo, Xugang
Abstract : Bithiophene imide (BTI) is a promising building block for constructing n‐type organic semiconductors. The β‐ positions of thiophene in BTI offer an exceptional opportunity for further structural expansion and optimization. Herein, a novel fluorinated BTI, s‐FBTI2, is designed and successfully synthesized, and its incorporation into a polymer backbone led to the resulting semiconductor s‐FBTI2‐FT with improved polymer backbone planarity enabled by the intramolecular non‐covalent S···F interactions and optimized electronic structure attributed to the high electronegativity of F atoms. When applied in organic thin‐film transistors (OTFTs), s‐FBTI2‐FT shows a unipolar n‐type transport with a remarkable electron mobility approaching 3.0 cm 2 V −1 s −1, which is >3‐fold higher than that of the polymer analogue without F. Moreover, all‐polymer solar cells (all‐PSCs) with s‐FBTI2‐FT as the electron acceptor polymer achieve a power conversion efficiency of 6.50% with a remarkably high open‐circuit voltage of 1.04 V, which is substantially greater than that of solar cells based on the nonfluorinated analogue acceptor showing negligible photovoltaic performance. The results demonstrate that s‐FBTI‐FT is one of best‐performing n‐type polymer semiconductors reported till today in terms of both OTFT and all‐PSC performances, and fluorination offers an effective approach for optimizing optoelectronic properties of BTI‐based polymers for device performance improvement. Abstract : The β ‐position of bithiophene imide is modified by incorporating F atoms to generate a novel building block s‐FBTI2, a well desired "stronger acceptor" for developing electron‐transporting semiconductors. The polymer s‐FBTI2‐FT shows a remarkable electron mobility approaching 3.0 cm 2 V −1 s −1 in organic thin‐film transistors and a highly promising power conversion efficiency of 6.50% in all‐polymer solar cells.